Preparation method of zinc selenide substrate 7-14 [mu] m antireflection film system

By plating eight-layer film layers of Ge, ZnSe, YbF3 and ZnS on the zinc selenide substrate of infrared optical coating, the problem of insufficient transmittance in the wide band range in the prior art was solved, and 7 The high transmittance of the -14μm band and the extremely high transmittance of the 8-12μm band meet the needs of improving infrared performance.

CN119243093APending Publication Date: 2025-01-03安徽光智科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411257989.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing infrared optical coatings are difficult to maintain high transmittance in a wider band range, especially in the 7-14μm band, which affects the improvement of infrared performance.

Method used

Using an urgency film system with zinc selenide substrate, eight film layers of different thicknesses composed of four film materials, Ge, ZnSe, YbF3, and ZnS, are plated on both sides of the lens, using vacuum coating technology and ion source assistance. The thickness and deposition rate of each film layer are controlled to ensure that the average transmittance in the 7-14 μm band reaches more than 95%, and the average transmittance in the 8-12 μm band reaches more than 97.5%.

Benefits of technology

It achieves high transmittance in a wider band range, meets the needs of improving infrared performance, and verifies the adhesion and stability of the membrane system through testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243093A_ABST
    Figure CN119243093A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a zinc selenide substrate 7-14 [mu] m antireflection film system. The preparation method comprises the following steps: S1, cleaning a plating accompanying sheet of a zinc selenide substrate serving as a lens and the surface of a product; s2, putting the lens into an oven; s3, putting the lens into a tool clamp, and hanging the tool clamp into the cavity; s4, vacuumizing, and opening an ion source for auxiliary coating of the vacuum coating machine for cleaning; s5, maintaining the vacuum degree, evaporating a first Ge film layer on the first surface of the lens, and assisting with an ion source; s6, evaporating a first ZnSe film layer with the assistance of an ion source; s7, evaporating a second Ge film layer with the assistance of an ion source; s8, evaporating a second ZnSe film layer with the assistance of an ion source; s9, evaporating a third Ge film layer with the assistance of an ion source; s10, evaporating a third ZnSe film layer with the assistance of an ion source; s11, evaporating a YbF3 film layer with the assistance of an ion source; s12, evaporating a ZnS film layer with the assistance of an ion source; s13, cooling is conducted, and the tool clamp, the accompanying plating piece and the product are taken out; and S14, the step S1 to the step S13 are repeated, and evaporation is conducted on the opposite second face of the lens in sequence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of infrared materials, and more specifically to a method for preparing a 7-14 μm anti-reflection film system on a zinc selenide substrate. Background Art

[0002] In the field of infrared optical coatings, zinc selenide windows have a wide transmission band and are not afraid of water. They are widely used in infrared spectrometers, spectrophotometers, and prisms, transmission windows, and lenses of infrared devices.

[0003] The increasing demand for infrared performance is to maintain high transmittance over a wider wavelength range. Summary of the invention

[0004] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for preparing a 7-14μm antireflection film system on a zinc selenide substrate, wherein the average transmittance in the 7-14μm band is above 95% and the average transmittance in the 8-12μm band is above 97.5%.

[0005] Thus, a method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate comprises the following steps: S1, cleaning the surface of the accompanying plating sheet and the product of the zinc selenide substrate as the lens, wherein the thickness of the accompanying plating sheet is 2.0±0.1 mm; S2, placing the cleaned lens into an oven, setting the temperature of the oven to 120±10°C, and baking for 2-2.5 hours; S3, placing the baked lens into a fixture, and hanging the fixture with the lens placed into the cavity of a vacuum coating machine, and setting the temperature of the cavity to 120-130°C; S4, starting the vacuum coating machine to evacuate, and the vacuum degree reaches 1.5×10 -3Pa, turn on the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.0-2.5A, and the emitter current is 1.3-1.5A; S5, maintain the aforementioned vacuum degree, evaporate the first Ge film layer on the first surface of the lens, the deposition rate of the first Ge film layer is 0.4nm / s, the film thickness of the first Ge film layer is controlled to be 44nm±2nm, and the ion source is used for assisted evaporation; S6, evaporate the first ZnSe film layer on the plated first Ge film layer, the deposition rate of the first ZnSe film layer is 0.8nm / s, the film thickness of the first ZnSe film layer is controlled to be 641.6nm±5nm, and the ion source is used for assisted evaporation; S7, evaporate the second Ge film layer on the plated first ZnSe film layer, the deposition rate of the second Ge film layer is 0.4nm / s, and the second Ge film is controlled to be The thickness of the layer is 93.4nm±4nm, and ion source assisted evaporation is adopted; S8, a second ZnSe film layer is evaporated on the plated second Ge film layer, the deposition rate of the second ZnSe film layer is 0.8nm / s, and the film thickness of the second ZnSe film layer is controlled to be 417.7nm±5nm, and ion source assisted evaporation is adopted; S9, a third Ge film layer is evaporated on the plated second ZnSe film layer, the deposition rate of the third Ge film layer is 0.4nm / s, and the film thickness of the third Ge film layer is controlled to be 92.1nm±4nm, and ion source assisted evaporation is adopted; S10, a third ZnSe film layer is evaporated on the plated third Ge film layer, the deposition rate of the third ZnSe film layer is 0.8nm / s, and the film thickness of the third ZnSe film layer is controlled to be 1192.6nm±5nm, and ion source assisted evaporation is adopted; S11, YbF is evaporated on the plated third ZnSe film layer 3 Film, YbF 3 The film deposition rate is 0.6nm / s, controlling the YbF 3 The film thickness is 1140nm±5nm, and the ion source assisted evaporation is adopted; S12, on the plated YbF 3 A ZnS film layer is evaporated on the film layer, the deposition rate of the ZnS film layer is 0.8nm / s, the film thickness of the ZnS film layer is controlled to be 145.6nm±5nm, and ion source assisted evaporation is adopted; S13, after the ZnS film layer is plated, the tooling fixture together with the accompanying plated sheet and the product are taken out after the chamber is cooled to below 60°C; S14, steps S1 to S13 are repeated, and the first Ge film layer, the first ZnSe film layer, the second Ge film layer, the second ZnSe film layer, the third Ge film layer, the third ZnSe film layer, the YbF 3 Film layer, ZnS film layer.

[0006] The beneficial effects of the present invention are as follows: In the preparation method of the 7-14 μm antireflection film system of the zinc selenide substrate disclosed by the root, the same Ge, ZnSe, YbF 3 The anti-reflection film system consists of eight film layers of different thicknesses made of four kinds of film materials, namely, ZnS. As verified by the co-plating film in the test process described later, the average transmittance in the 7-14μm band is more than 95%, and the average transmittance in the 8-12μm band is more than 97.5%. That is, it not only ensures the extremely high average transmittance in the 8-12μm band, but also has an excellent average transmittance in the extended 7-14μm band, thereby meeting the requirements of infrared performance in a wider band range. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 It is a schematic structural diagram of a 7-14 μm anti-reflection film system coated on both sides of a co-plating sheet and a product including a zinc selenide substrate according to the preparation method of the 7-14 μm anti-reflection film system on a zinc selenide substrate disclosed in the present invention.

[0008] Figure 2 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 coated with 7-14 μm anti-reflection film system on both sides in the 7-14 μm band.

[0009] Figure 3 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 coated with 7-14 μm anti-reflection film system on both sides in the 8-12 μm band. DETAILED DESCRIPTION

[0010] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0011] [Preparation method of 7-14μm antireflection film system on zinc selenide substrate]

[0012] The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate disclosed in the present invention comprises the following steps:

[0013] S1, cleaning the surface of the accompanying plating sheet and the product as the zinc selenide substrate of the lens, the thickness of the accompanying plating sheet is 2.0±0.1mm;

[0014] S2, putting the cleaned lens into an oven, setting the temperature of the oven to 120±10℃, and baking for 2-2.5h;

[0015] S3, putting the baked lens into the fixture, and hanging the fixture with the lens into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 120-130℃;

[0016] S4, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, turn on the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.0-2.5A, and the emitter current is 1.3-1.5A;

[0017] S5, maintaining the aforementioned vacuum degree, evaporating a first Ge film layer on the first surface of the lens, the deposition rate of the first Ge film layer is 0.4 nm / s, the film thickness of the first Ge film layer is controlled to be 44 nm±2 nm, and ion source assisted evaporation is used;

[0018] S6, evaporating a first ZnSe film layer on the plated first Ge film layer, the deposition rate of the first ZnSe film layer is 0.8 nm / s, the film thickness of the first ZnSe film layer is controlled to be 641.6 nm±5 nm, and ion source assisted evaporation is adopted;

[0019] S7, evaporating a second Ge film layer on the plated first ZnSe film layer, the deposition rate of the second Ge film layer is 0.4 nm / s, the film thickness of the second Ge film layer is controlled to be 93.4 nm±4 nm, and ion source assisted evaporation is adopted;

[0020] S8, evaporating a second ZnSe film layer on the plated second Ge film layer, the deposition rate of the second ZnSe film layer is 0.8 nm / s, the film thickness of the second ZnSe film layer is controlled to be 417.7 nm±5 nm, and ion source assisted evaporation is adopted;

[0021] S9, evaporating a third Ge film layer on the plated second ZnSe film layer, the deposition rate of the third Ge film layer is 0.4 nm / s, the film thickness of the third Ge film layer is controlled to be 92.1 nm±4 nm, and ion source assisted evaporation is adopted;

[0022] S10, evaporating a third ZnSe film layer on the plated third Ge film layer, the deposition rate of the third ZnSe film layer is 0.8 nm / s, the film thickness of the third ZnSe is controlled to be 1192.6 nm±5 nm, and ion source assisted evaporation is adopted;

[0023] S11, evaporating YbF on the plated third ZnSe film layer 3 Film, YbF 3 The film deposition rate is 0.6nm / s, controlling the YbF 3 The film thickness of the film layer is 1140nm±5nm, and ion source assisted evaporation is used;

[0024] S12, on plated YbF 3 A ZnS film layer is deposited on the film layer, the deposition rate of the ZnS film layer is 0.8 nm / s, the film thickness of the ZnS film layer is controlled to be 145.6 nm±5 nm, and ion source assisted evaporation is adopted;

[0025] S13, after the ZnS film is plated, the cavity is cooled to below 60°C and the fixture, the accompanying plated sheet and the product are taken out;

[0026] S14, repeating steps S1 to S13, sequentially depositing a first Ge film layer, a first ZnSe film layer, a second Ge film layer, a second ZnSe film layer, a third Ge film layer, a third ZnSe film layer, and YbF 3 Film layer, ZnS film layer.

[0027] In the preparation method of the 7-14 μm antireflection film system on the zinc selenide substrate disclosed in the root, the same Ge, ZnSe, YbF 3 The anti-reflection film system consists of eight film layers of different thicknesses made of four kinds of film materials, namely, ZnS. As verified by the co-plating film in the test process described later, the average transmittance in the 7-14μm band is more than 95%, and the average transmittance in the 8-12μm band is more than 97.5%. That is, it not only ensures the extremely high average transmittance in the 8-12μm band, but also has an excellent average transmittance in the extended 7-14μm band, thereby meeting the requirements of infrared performance in a wider band range.

[0028] In the preparation method of the 7-14 μm antireflection film system of the zinc selenide substrate disclosed in the root, the eight film layers plated on each surface are three Ge film layers, three ZnSe film layers, one YbF 3 The film layer is composed of a ZnS film layer, Ge film layers and ZnSe film layers alternately, the first Ge film layer is located on the zinc selenide base, ZnS is located on the outermost layer, and YbF 3 The membrane layer is located in the second outer layer.

[0029] In the method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate disclosed in the root, the total thickness of the eight film layers plated on each surface is 3767 nm±35 nm.

[0030] The surface cleaning in step S1 is beneficial to improving the surface conditions of the first and second surfaces of the accompanying plate and the product, and is helpful to improving the bonding performance of the anti-reflection film system on each surface with the corresponding surface of the accompanying plate and the product. For example, the surface of the lens is cleaned by ultrasonic or hand wiping.

[0031] In one example, in step S1 , the thickness of the accompanying plating sheet is 2.0 mm.

[0032] The baking in step S2 shortens the time for the vacuum coating machine to reach a set cavity temperature in step S3, thereby improving the preparation efficiency.

[0033] The temperature setting of the vacuum coating machine in step S3 heats the lens through the cavity of the coating machine, which helps the growth of the first Ge film layer and reduces the growth stress of the first Ge film layer.

[0034] In one example, in step S3, the temperature of the chamber is set to 130°C.

[0035] In step S4, an ion source is used for cleaning. The bombardment and sputtering of argon ions ionized by a working gas such as argon gas will cause the impurities, oil molecules, and oxides adsorbed on the surface of each surface of the accompanying coating sheet and the product to separate from the substrate surface, thereby greatly improving the interface state and helping to improve the bonding performance between the first Ge film layer and the zinc selenide substrate. At the same time, through the bombardment of argon ions on each surface of the zinc selenide substrate, each surface of the zinc selenide substrate can be heated, which is conducive to the growth of the first Ge film layer and reduces the growth stress of the first Ge film layer.

[0036] In one example, in step S4, the ion source is a Hall ion source, and argon gas is used as the working gas.

[0037] In one example, in step S4 , the anode current is 1.2A and the emitter current is 1.5A.

[0038] In one example, in step S5, the thickness of the first Ge film layer is controlled to be 44 nm; in step S6, the thickness of the first ZnSe film layer is controlled to be 641.6 nm; in step S7, the thickness of the second Ge film layer is controlled to be 93.4 nm; in step S8, the thickness of the second ZnSe film layer is controlled to be 417.7 nm; in step S9, the thickness of the third Ge film layer is controlled to be 92.1 nm; in step S10, the thickness of the third ZnSe film layer is controlled to be 1192.6 nm; in step S11, the thickness of the YbF 3 The film thickness of the film layer is 1140 nm; in step S12, the film thickness of the ZnS film layer is controlled to be 145.6 nm.

[0039] In one example, in step S5, step S7 and step S9 (i.e. for the Ge film layer), the evaporation is performed by electron beam evaporation; in step S6, step S8, step S10, step S11 and step S12 (i.e. for the ZnSe film layer, YbF 3 In the film layer and ZnS film layer), resistance heating evaporation is used for evaporation.

[0040] In one example, in step S5, step S7 and step S9 (for the Ge film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5A, argon gas is used to form the neutralization gas, and the neutralization gas flow rate is 10sccm; the anode voltage of the ion source is 150V, the anode current is 1.2A, argon gas is used as the working gas, and the argon gas flow rate is 100sccm.

[0041] In one example, in step S6, step S8 and step S10 (for the ZnSe film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are: the neutralization current is 0.5A, argon is used to form the neutralization gas, and the flow rate of the neutralization gas is 8sccm; the anode voltage of the ion source is 100V, the anode current is 1.0A, argon is used as the working gas, and the flow rate of argon is 100sccm.

[0042] In one example, in step S11 (for YbF 3 In the membrane layer, a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.6A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 130V, the anode current is 1.3A, argon and oxygen are used as working gases, the flow rate of argon is 30sccm, and the flow rate of oxygen is 70sccm.

[0043] In one example, in step S12 (for the ZnS film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5A, argon gas is used to form the neutralization gas, and the flow rate of the neutralization gas is 8sccm; the anode voltage of the ion source is 100V, the anode current is 1.0A, argon gas is used as the working gas, and the flow rate of argon gas is 100sccm.

[0044] In the above example using a neutralizer, the working gas of the ion source will form a near plasma, but these plasmas may contain excess charged ions, and the neutralizing gas in the neutralizer neutralizes the excess charged ions generated by the ion source by ionizing to form electrons, thereby eliminating the influence of the charged ions on the film layer of the evaporated film, thereby ensuring the quality of each film layer assisted by ion source evaporation. Therefore, this effect can be achieved only at a very small flow ratio (1 / 10 or 1 / 12.5) of the neutralizing gas:working gas.

[0045] [test]

[0046] Example 1

[0047] The preparation method of the 7-14μm antireflection film system on a zinc selenide substrate adopts the following steps:

[0048] S1, the surface of the accompanying plating sheet and the product as the zinc selenide substrate of the lens is cleaned by ultrasonic wave, and the thickness of the accompanying plating sheet is 2.0 mm;

[0049] S2, putting the cleaned lens into an oven, setting the temperature of the oven to 120°C, and baking for 2 hours;

[0050] S3, putting the baked lens into a fixture, and hanging the fixture with the lens into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C;

[0051] S4, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, the auxiliary coating ion source of the vacuum coating machine is turned on for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.2A, and the emitter current is 1.5A. The vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer manufactured and sold by Chengdu Xiwok Vacuum Technology Co., Ltd. The Hall ion source equipped with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd., and the Hall ion source uses argon as the working gas;

[0052] S5, maintaining the aforementioned vacuum degree, evaporating a first Ge film layer on the first surface of the lens, the deposition rate of the first Ge film layer is 0.4nm / s, the film thickness of the first Ge film layer is controlled to be 44nmnm, and the evaporation is carried out by electron beam evaporation and ion source assisted evaporation;

[0053] S6, evaporating a first ZnSe film layer on the plated first Ge film layer, the deposition rate of the first ZnSe film layer is 0.8nm / s, the film thickness of the first ZnSe film layer is controlled to be 641.6nmnm, the evaporation is carried out by resistance heating evaporation, and ion source assisted evaporation is adopted;

[0054] S7, evaporating a second Ge film layer on the plated first ZnSe film layer, the deposition rate of the second Ge film layer is 0.4 nm / s, the film thickness of the second Ge film layer is controlled to be 93.4 nmnm, and the evaporation is performed by electron beam evaporation and ion source assisted evaporation;

[0055] S8, evaporating a second ZnSe film layer on the plated second Ge film layer, the deposition rate of the second ZnSe film layer is 0.8nm / s, the film thickness of the second ZnSe film layer is controlled to be 417.7nmnm, the evaporation is carried out by resistance heating evaporation, and ion source assisted evaporation is adopted;

[0056] S9, evaporating a third Ge film layer on the plated second ZnSe film layer, the deposition rate of the third Ge film layer is 0.4 nm / s, the film thickness of the third Ge film layer is controlled to be 92.1 nmnm, and the evaporation is performed by electron beam evaporation and ion source assisted evaporation;

[0057] S10, vapor-depositing a third ZnSe film layer on the plated third Ge film layer, the deposition rate of the third ZnSe film layer is 0.8 nm / s, the film thickness of the third ZnSe is controlled to be 1192.6 nmnm, the vapor deposition adopts resistance heating evaporation, and adopts ion source assisted vapor deposition;

[0058] S11, evaporating YbF on the plated third ZnSe film layer 3 Film, YbF 3 The film deposition rate is 0.6nm / s, controlling the YbF 3 The film thickness of the film layer is 1140nmnm, and the evaporation is carried out by resistance heating evaporation and ion source assisted evaporation;

[0059] S12, on plated YbF 3 A ZnS film layer is evaporated on the film layer, the deposition rate of the ZnS film layer is 0.8 nm / s, the film thickness of the ZnS film layer is controlled to be 145.6 nmnm, the evaporation is carried out by resistance heating evaporation, and an ion source is used to assist the evaporation;

[0060] S13, after the ZnS film is plated, wait for the cavity to cool to 60°C and take out the fixture together with the accompanying plated sheet and the product;

[0061] S14, repeating steps S1 to S13, sequentially depositing a first Ge film layer, a first ZnSe film layer, a second Ge film layer, a second ZnSe film layer, a third Ge film layer, a third ZnSe film layer, and YbF 3 Film layer, ZnS film layer;

[0062] Among them, in step S5, step S7 and step S9 (for the Ge film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.5A, argon is used to form the neutralization gas, the neutralization gas flow rate is 10sccm, the anode voltage of the ion source is 150V, the anode current is 1.2A, argon is used as the working gas, and the argon gas flow rate is 100sccm;

[0063] Wherein, in step S6, step S8 and step S10 (for the ZnSe film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.5A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 100V, the anode current is 1.0A, argon is used as the working gas, and the flow rate of the argon gas is 100sccm;

[0064] In step S11 (for YbF 3In the film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.6A, argon is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 130V, the anode current is 1.3A, argon and oxygen are used as working gases, the flow rate of argon is 30sccm, and the flow rate of oxygen is 70sccm;

[0065] Among them, in step S12 (for the ZnS film layer), a neutralizer is provided for the ion source, and the parameters of the neutralizer are: the neutralization current is 0.5A, argon is used to form the neutralization gas, and the flow rate of the neutralization gas is 8sccm. The anode voltage of the ion source is 100V, the anode current is 1.0A, argon is used as the working gas, and the flow rate of argon is 100sccm.

[0066] The structure of the same antireflection film system coated on both sides prepared in Example 1 is as follows Figure 1 shown. Figure 2 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 coated with 7-14 μm anti-reflection film system on both sides in the 7-14 μm band. Figure 3 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 coated with 7-14 μm anti-reflection film system on both sides in the 8-12 μm band.

[0067] from Figure 3 It can be seen that in the 8-12 μm band, the average transmittance (arithmetic mean) reaches 97.74% (ie, above 97.5%), and in the extended 7-14 μm band, the average transmittance reaches 95.28% (ie, above 95%).

[0068] According to the content of GJB2485-95 General Specification for Optical Coatings, the overall performance of the accompanying coating together with the anti-reflection coating on both sides is tested.

[0069] Water bubble test: The accompanying plate prepared in Example 1 together with the anti-reflection films on both sides were subjected to a water bubble test with tap water for 10 minutes. No anti-reflection film was found to fall off the accompanying plate, and no anti-reflection film was found to be cracked.

[0070] Adhesion test: After the bubble test with tap water is completed, 3M tape is pasted on the anti-reflection film system on the first side of the co-plating film by hand, and the tape is pulled in the direction opposite to the pasting end, but the anti-reflection film system is not pulled up; for the second side of the co-plating film, 3M tape is pasted on the anti-reflection film system on the second side of the co-plating film by hand, and the tape is pulled in the direction opposite to the pasting end, but the anti-reflection film system is not pulled up.

[0071] The water bubble test and tape pulling test show that the anti-reflection film system on both sides of the accompanying coating film has good adhesion.

[0072] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate, characterized in that: Includes steps: S1, cleaning the surface of the accompanying plating sheet and the product as the zinc selenide substrate of the lens, the thickness of the accompanying plating sheet is 2.0±0.1mm; S2, putting the cleaned lens into an oven, setting the temperature of the oven to 120±10℃, and baking for 2-2.5h; S3, putting the baked lens into the fixture, and hanging the fixture with the lens into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 120-130℃; S4, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, turn on the auxiliary coating ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the anode voltage of the ion source is 220V, the anode current is 1.0-2.5A, and the emitter current is 1.3-1.5A; S5, maintaining the aforementioned vacuum degree, evaporating a first Ge film layer on the first surface of the lens, the deposition rate of the first Ge film layer is 0.4 nm / s, the film thickness of the first Ge film layer is controlled to be 44 nm±2 nm, and ion source assisted evaporation is used; S6, evaporating a first ZnSe film layer on the plated first Ge film layer, the deposition rate of the first ZnSe film layer is 0.8 nm / s, the film thickness of the first ZnSe film layer is controlled to be 641.6 nm±5 nm, and ion source assisted evaporation is adopted; S7, evaporating a second Ge film layer on the plated first ZnSe film layer, the deposition rate of the second Ge film layer is 0.4 nm / s, the film thickness of the second Ge film layer is controlled to be 93.4 nm±4 nm, and ion source assisted evaporation is adopted; S8, evaporating a second ZnSe film layer on the plated second Ge film layer, the deposition rate of the second ZnSe film layer is 0.8 nm / s, the film thickness of the second ZnSe film layer is controlled to be 417.7 nm±5 nm, and ion source assisted evaporation is adopted; S9, evaporating a third Ge film layer on the plated second ZnSe film layer, the deposition rate of the third Ge film layer is 0.4 nm / s, the film thickness of the third Ge film layer is controlled to be 92.1 nm±4 nm, and ion source assisted evaporation is adopted; S10, evaporating a third ZnSe film layer on the plated third Ge film layer, the deposition rate of the third ZnSe film layer is 0.8 nm / s, the film thickness of the third ZnSe is controlled to be 1192.6 nm±5 nm, and ion source assisted evaporation is adopted; S11, evaporating a YbF3 film layer on the plated third ZnSe film layer, the deposition rate of the YbF3 film layer is 0.6 nm / s, the film thickness of the YbF3 film layer is controlled to be 1140 nm±5 nm, and ion source assisted evaporation is adopted; S12, evaporating a ZnS film layer on the plated YbF3 film layer, the deposition rate of the ZnS film layer is 0.8 nm / s, the film thickness of the ZnS film layer is controlled to be 145.6 nm±5 nm, and ion source assisted evaporation is adopted; S13, after the ZnS film is plated, the cavity is cooled to below 60°C and the fixture, the accompanying plated sheet and the product are taken out; S14, repeat steps S1 to S13, and sequentially evaporate a first Ge film layer, a first ZnSe film layer, a second Ge film layer, a second ZnSe film layer, a third Ge film layer, a third ZnSe film layer, a YbF3 film layer, and a ZnS film layer on the second opposite side of the lens.

2. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S1, the thickness of the accompanying plating sheet is 2.0 mm.

3. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S1, the surface of the lens is cleaned by ultrasonic wave or hand wiping.

4. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S3, the temperature of the chamber is set to 130°C.

5. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S4, the anode current is 1.2A and the emitter current is 1.5A.

6. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S4, the ion source is a Hall ion source.

7. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S5, the film thickness of the first Ge film layer is controlled to be 44 nm; In step S6, the film thickness of the first ZnSe film layer is controlled to be 641.6 nm; In step S7, the film thickness of the second Ge film layer is controlled to be 93.4 nm; In step S8, the film thickness of the second ZnSe film layer is controlled to be 417.7 nm; In step S9, the thickness of the third Ge film layer is controlled to be 92.1 nm; In step S10, the film thickness of the third ZnSe is controlled to be 1192.6 nm; In step S11, the film thickness of the YbF3 film is controlled to be 1140 nm; In step S12, the film thickness of the ZnS film layer is controlled to be 145.6 nm.

8. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S5, step S7 and step S9, the evaporation is performed by electron beam evaporation; In step S6 , step S8 , step S10 , step S11 , and step S12 , the vapor deposition is performed by resistance heating evaporation.

9. The method for preparing a 7-14 μm antireflection film system on a zinc selenide substrate according to claim 1, characterized in that: In step S5, step S7 and step S9, a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.5A, argon is used to form the neutralization gas, the neutralization gas flow rate is 10sccm, the anode voltage of the ion source is 150V, the anode current is 1.2A, argon is used as the working gas, and the argon gas flow rate is 100sccm; In step S6, step S8 and step S10, a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: the neutralization current is 0.5A, argon gas is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 100V, the anode current is 1.0A, argon gas is used as the working gas, and the flow rate of the argon gas is 100sccm; In step S11, a neutralizer is provided for the ion source, and the parameters of the neutralizer are as follows: a neutralization current of 0.6A, argon gas is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 130V, the anode current is 1.3A, argon gas and oxygen are used as working gases, the flow rate of argon gas is 30sccm, and the flow rate of oxygen is 70sccm; In step S12, a neutralizer is provided for the ion source, and the parameters of the neutralizer are: a neutralization current of 0.5A, argon gas is used to form the neutralization gas, the flow rate of the neutralization gas is 8sccm, the anode voltage of the ion source is 100V, the anode current is 1.0A, argon gas is used as the working gas, and the flow rate of argon gas is 100sccm.

Citation Information

Patent Citations

  • Germanium substrate 8-12 [mu] m infrared band diaphragm and preparation method thereof

    CN114200552A

  • Preparation method for plating antireflection film system on chalcogenide glass substrate

    CN116282962A

  • Preparation method for plating double-waveband antireflection film on zinc selenide substrate

    CN117448751A